Analysis of Availability of Infrastructure to Support Performance Power Education Agro Complex in University Hasanuddin - Wahyudie Suratman; Rosady Mulyadi; Idawarni J. Asmal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Infrastructure is an important and main component in the running of work activities at the Hasanuddin University Agro Complex. Work cannot be completed quickly and easily by education personnel without the assistance of adequate infrastructure. Therefore, the existence of infrastructure will certainly affect the performance of education personnel. So, the availability of infrastructure is very influential on the performance of education personnel at the Agro Complex, Hasanuddin University. The objectives of this study are (1) to determine and analyze whether the existing infrastructure in the Hasanuddin University Agro Complex has met the infrastructure standards of the SPN, (2) to determine and analyze the perception of education personnel on the existing infrastructure in the Hasanuddin University Agro Complex, and (3 ) to determine and analyze the effect of existing infrastructure in the Agro Complex of Hasanuddin University on the performance of education personnel.This study uses a correlational quantitative research design. The researcher chose the research location in the Hasanuddin University Complex Agro Clump which is located at Jalan Perintis Kemerdekaan km 10, Tamalanrea Indah, Tamalanrea, Makassar, South Sulawesi. The research time was carried out for 6 months starting from July 2021 to December 2021. Sampling used the slovin formula, and the results of the sample were 64 people. Data were collected through questionnaires and analyzed using a simple linear regression technique with the help of the Statistical Packages for Social Sciences (SPSS) release 23.0 program.The results showed that (1) the existing infrastructure in the Hasanuddin University Agro Complex had met the infrastructure standards of the SPN, (2) the education staff's perception of the existing infrastructure in the Hasanuddin University Agro Complex was classified as very good, and (3) there was an influence on the existing infrastructure. at the Hasanuddin University Agro Complex on the performance of education personnel.